Evaluation of Carotid Stenosis in a High‐Stroke‐Risk Population by Hemodynamic Dual‐Parameters Based on Ultrasound Vector Flow Imaging - Shaofu Hong; Yinghui Dong; Wenjing Gao; Di Song; Mengmeng Liu; Weiyue Li; Yigang Du; Jinfeng Xu; Fajin Dong (Brain and Behavior)
ABSTRACT Objective This study explored the feasibility of using high‐frame‐rate ultrasound vector flow imaging (VFI) to quantitatively assess hemodynamics in atherosclerotic internal carotid artery stenosis (ICAS) by evaluating dual‐parameters, turbulence index (Tur), and wall shear stress (WSS). Their efficacy in evaluating carotid artery stenosis was also analyzed. Methods Fifty‐nine patients with ICAS were enrolled. B‐mode ultrasound and V Flow (a high‐frame‐rate VFI) were performed using the Resona R9 system. The stenosis rate was measured in grayscale mode, whereas the time‐averaged Tur index, the time‐averaged WSS (WSSmean), and maximum WSS (WSSmax) around stenosis were measured. The combined diagnostic efficacy of Tur inand WSS was also investigated. Results Compared to proximal to stenosis (Tur index, 2.88% ± 3.65%), highly disordered blood flow was observed in the stenotic (23.17% ± 15.52%, p < 0.001) and distal segment (25.86% ± 17.29%, p < 0.001). WSSmax ([11.91 ± 6.73] vs. [4.43 ± 5.4] Pa, p < 0.001) and WSSmean ([3.42 ± 2.67] vs. [0.86 ± 1.21] Pa, p < 0.001) were significantly bigger in stenotic than those in the distal segment. The differences in the ratio WSSmax/Tur or WSSmean/Tur among different segments around stenosis were statistically significant (p < 0.001). The combination of Tur index and WSS had the best diagnostic performance in ICAS (AUC, 0.899). Conclusion The application of Tur index and WSS for quantitative assessment of ICAS hemodynamic changes is feasible, with the combined evaluation of these two parameters providing incremental diagnostic value for carotid artery stenosis. VFI‐based dual quantitative parameters may offer promising noninvasive diagnostic tools for carotid artery stenosis in high‐stroke‐risk populations.